A Pragmatic Study of Medical Proverbs in English With Reference To Arabic - Al-Khazragy, Sayf H. Abdalhakeem (دار الأطروحة للنشر العلمي, 2016)
This thesis is a pragmatic study of medical proverbs in English with reference to Arabic. The underlying general aim of the study is to analyze the speech acts of the selected medical proverbs and to identify the cooperative principles of Grice (Grice's maxims) and ways of flouting these maxims. As long as medical proverbs can be embedded in the flow of conversations, they may flout one or more than one of Grice's maxims. Medical proverbs serve different functions and achieve different illocutionary acts. They are sometimes said to mean something different in addition to what is explicitly stated. Words may mean something beyond those intended by the addressor. These extra meanings might achieve or refer to different illocutionary acts. Four hypotheses are proposed for testing this possibility. They are as follows: 1-The indirect speech acts of English medical proverbs are directives and assertives. And there is a cooccurrence between these types of speech acts and the flouting of the quality maxim. 2-Medical proverbs are related to certain felicity conditions which prevent their relevant acts from disharmonizing. They contain everyday experience and common observation in succinct and formulaic language making them easy to remember and ready to be used instantly. 3-Grice's maxim of quality is the most flouted cooperative principle and it has been flouted mainly by the use of metaphor. 4-Medical proverbs are sometimes used pragmatically and this is for the purpose of the addressor's linguistic production. And passive constructions are not anticipated in the medical proverbs. The data consist of thirty medical proverbs, twenty in English and ten in Arabic. Concerning the English medical proverbs, these proverbs are applied to imaginary conversations created by the researcher in order to clarify the idea and to reach the intended meaning of the addressor. However, Arabic medical proverbs are analyzed directly in order to reach the intended meaning of the addressor. Moreover, the analysis of flouting has been based upon Grice's model (1975), the analysis of speech acts has been based upon Searle's (1979), and the analysis of the Arabic data has been based upon the model of Al-Sakakki (1981), Al-Jurjaani (1982), Ash- Sheikh Hassan (1986), As-Siyouti (1988) and Al- Akoob et al (1993). The pragmalinguistic analysis of the corpus has verified the validity of the four hypotheses above. In addition, it has yielded the following general findings: 1-Grice's cooperative principle and its relevant maxims have been flouted in most of the analyzed English medical proverbs 2-The maxim of quality has been flouted mainly by using metaphor as it is evident in many analyzed proverbs 3-English medical proverbs have the indirect speech acts of directives and assertives which are realized in simple, active, and declarative sentences. 4-All the Arabic medical proverbs are constative speech acts directed to an open-minded person. Owing to the importance of medical proverbs in our daily life as well as the teaching environment, this study undertakes certain pedagogical implications and suggestions for further research.
Keywords: المصطلحات الطبية -- اللغة الإنجليزية -- اللغة العربية